The impact of fiscal policy on the Philippine labor market: An SVAR approach - Sobrepeña, Valerie Marie V. (Animo Repository, 2018)
This paper reviews existing studies that analyze the effects of fiscal expansion on the Philippine labor market. In this study, we use public sector wages to represent fiscal policy. This allows me to study the effects of changes in government spending on the labor market in the Philippines by using a structural vector auto regression (SVAR) model. This study uses quarterly data for the period 2000 - 2017, which are obtained from different government agencies. Impulse response functions were used to examine the degree of shock persistence observed for key labor market outcomes such as private sector wages, total hours of work, job separation. Our empirical results show that shocks to public sector wages increase gross domestic product, private consumption, and private sector employment in the short-run, but understandably decline in the long-run. We also find that expanding the fiscal program reduces the unemployment rate and government employment rate in the short-run but rises government employment rate in the long-run. The response of private sector wage to a fiscal shock is negative. While private sector vacancy has no direct response on fiscal shocks, vacancy in the government sector declines. The results show that increases in government wage are necessary to motivate government employees to render better services that are useful to the private sector. However, one also needs to understand that a sustained increase in government wage bill has the potential of introducing distortions in the labor market, especially when the increase in public sector employment is deficit – financed or comes at the expense of private labor markets.